(untitled) (Scientific journal of the Fergana State University, 2023)
The connotations of a particular language subject are strongly influenced by various cultural, environmental, social, religious, and political factors, as opposed to its denotations. Accordingly, any analysis of the connotations of linguistic elements provides insight to understand language-specific parameters and to identify nonlinguistic similarities and differences between languages. The study of the metaphorical use of ornithonyms can shed light on language-specific cultural models that refer to connotations of specific animal terms to define human characteristics. An analysis of the use of bird name metaphors usually leads to an important understanding of the dominant cultural model of a particular society. This article discusses these issues and analyzes the features of the use of ornithonyms in two languages ​​in terms of differences and similarities.